2015
DOI: 10.1021/acsnano.5b05728
|View full text |Cite
|
Sign up to set email alerts
|

Active Sites Implanted Carbon Cages in Core–Shell Architecture: Highly Active and Durable Electrocatalyst for Hydrogen Evolution Reaction

Abstract: Low efficiency and poor stability are two major challenges we encounter in the exploration of non-noble metal electrocatalysts for the hydrogen evolution reaction (HER) in both acidic and alkaline environment. Herein, the hybrid of cobalt encapsulated by N, B codoped ultrathin carbon cages (Co@BCN) is first introduced as a highly active and durable nonprecious metal electrocatalysts for HER, which is constructed by a bottom-up approach using metal organic frameworks (MOFs) as precursor and self-sacrificing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
286
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 448 publications
(293 citation statements)
references
References 67 publications
7
286
0
Order By: Relevance
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 4 more Smart Citations
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
“…[22,59,61,62,64,74,78,79] During the past decade, synergistic coupling effects by the chemical substitution of some carbon atoms with two or more different kinds of heteroatoms have been shown. This is because the co-doping of two or more elements with reverse electronegativity into the carbon matrix can induce unique electron-donor properties.…”
Section: Multiple Heteroatom Co-dopingmentioning
confidence: 99%
See 3 more Smart Citations